The Influence of Profitability and Company Size on Earnings Quality with Capital Structure as an Intervening Variable - Pinem, Anwar Arifin; Rahmayuni, Siti; Jaya, Ekki Satria; Susanto, Ekko Edy; Azizah, Bintang Chairunnisa (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
The aim of this research is to determine the effect of profitability and company size on earnings quality by using capital structure as an intervening variable. The data used comes from the company's financial reports for 2011-2023. Profitability is measured by ROA and company size is measured by Ln (total assets), while earnings quality is calculated using the DACC formula acting as an intervening variable along with capital structure. The data analysis model used is multiple linear regression and path analysis. The findings show that profitability and company size have no influence on capital structure. Furthermore, the variables profitability, company size and capital structure have no effect on earnings quality, and capital structure does not act as a mediating variable between profitability and company size on earnings quality.